Enhancement of vitamin B6 levels in rice expressing Arabidopsis vitamin B6 biosynthesis de novo genes. (11th July 2019) - Mangel, Nathalie; Fudge, Jared B.; Li, Kuan‐Te; Wu, Ting‐Ying; Tohge, Takayuki; Fernie, Alisdair R.; Szurek, Boris; Fitzpatrick, Teresa B.; Gruissem, Wilhelm; Vanderschuren, Hervé
Summary: Vitamin B6 (pyridoxine) is vital for key metabolic reactions and reported to have antioxidant properties in planta . Therefore, enhancement of vitamin B6 content has been hypothesized to be a route to improve resistance to biotic and abiotic stresses. Most of the current studies on vitamin B6 in plants are on eudicot species, with monocots remaining largely unexplored. In this study, we investigated vitamin B6 biosynthesis in rice, with a view to examining the feasibility and impact of enhancing vitamin B6 levels. Constitutive expression in rice of two Arabidopsis thaliana genes from the vitamin B6 biosynthesis de novo pathway, At PDX1.1 and At PDX2, resulted in a considerable increase in vitamin B6 in leaves (up to 28.3‐fold) and roots (up to 12‐fold), with minimal impact on general growth. Rice lines accumulating high levels of vitamin B6 did not display enhanced tolerance to abiotic stress (salt) or biotic stress (resistance to Xanthomonas oryzae infection). While a significant increase in vitamin B6 content could also be achieved in rice seeds (up to 3.1‐fold), the increase was largely due to its accumulation in seed coat and embryo tissues, with little enhancement observed in the endosperm. However, seed yield was affected in some vitamin B6 ‐enhanced lines. Notably, expression of the transgenes did not affect the expression of the endogenous rice PDX genes. Intriguingly, despite transgene expression in leaves and seeds, the corresponding proteins were only detectable in leaves and could not be observed in seeds, possibly pointing to a mode of regulation in this organ. Significance Statement: We demonstrate that vitamin B6 can be enhanced in a monocot species (rice), leading to increased accumulation of unphosphorylated B6 vitamers and pyridoxine glucosides, particularly in leaves. Our analysis reveals current limitations and possibly regulatory mechanisms for vitamin B6 biosynthesis in rice endosperm.